Evaluasi Usability dengan Menerapkan Metode Heuristic Evaluation pada Website Dinas Pendidikan Kota Batu - Heraspati Yudha Pratama; Buce Trias Hanggara; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Batu City Education Office website is a website that provides a means of publishing and providing information and general descriptions regarding the Batu City Education Office. Based on the Regulation of the Minister of Communication and Information of the Republic of Indonesia Number 32 of 2017 concerning the Implementation of Portals and Websites of Government Agencies in Chapter X Monitoring and Evaluation Article 19 Paragraph (3) states "The implementation of monitoring and evaluation is carried out 1 time in 1 year or carried out at any time if needed". And also in the interview process mentioned that the website has never been evaluated. With opportunities based on local regulations, this research took place, for the user interface on the Batu City Education Office website. Because the Department of Education also feels that the appearance and some functions are considered less than satisfactory. In conducting the evaluation process on the website, using the heuristic evaluation method. In the evaluation process, it involves an expert user interface, which has a function in helping and assessing how the website can have a good design according to the heuristic evaluation rules. Before evaluating the need to discuss the problem by interviewing the relevant parties. Furthermore, an evaluation was carried out with the findings of usability problems, namely there were two problems found by the third evaluator. In the evaluation process the evaluator also has an assessment of the Batu City Education Office website with the highest average score of 3.6 for H-6 (Recognition rathen than recall) and the lowest is H-4 (Consistency and standards) with the acquisition of an average value. average 2.45. These findings are improved by making recommendations for improvement by applying the material design by google guidelines. recommendations based on the assessment are tested using a heuristic evaluation involving the same three evaluators in the evaluation process. Tests carried out to obtain these results are by reducing the severity value for each existing problem.